IMPLEMENTASI PELAYANAN TARIF RETRIBUSI PASAR DI PASAR CEMPAKA KECAMATAN PONTIANAK KOTA - Yoris Brageri E.01106112 (FISIP Universitas Tanjungpura, 2013)
This article is motivated by wanting to know the service charges at market rates by governments cempaka pontianak city. Author of this thesis limiting problem in the process of implementing relagulations pontianak city area number 4 of 2005 the levy withdrawal services market. Formulation of this research is ”How the implementation of market based services levy local regulation number 4 in 2005 the city of pontianak district cempaka market?”. As for the purpose of this research is to indentify and analyze about communication, resources, attitudes implementor, bureaucratic structure in the implementation of local regulations number 4 of 2005 on the withdrawal of market tax rates. Here the authors use research methods research deskriktif types and datacollection techniques used in this study is the observation, interviews, documentation . While the data analysis techniques diskriktif where collected data is processed and analyzed qualitatively. From the anaysis of the data shows that the results of the implementation of the levy collection services in the market has not reached the market Cempaka predetermined targets, but the implementation is quite good, is seen from the large number and the realization of the target number is not too large. Thus, it can be concluded that the implementation of market withdrawal services levy rates in the market can be said cempaka not run optimally, and to realize the local regulation number 4 in 2005 is expected performance of the officers need to be improved and more professional in carrying out their duties. Keywords: Serviceslevy, implementation, government regulations number 4 of 2005.